Does surgical timing affect the rapidity of recovery in deep pain‐entire non‐ambulatory dogs with thoracolumbar intervertebral disk extrusion?. (31st October 2022) - Vicens Zanoguera, L.; Pauciulo, C.; Corlazzoli, D.; Cauduro, A.; Motta, L.
Abstract : Objective: To investigate whether the delay between onset of neurological signs and spinal cord decompression affects the time to recovery in non‐ambulatory paraparetic/paraplegic dogs with deep pain perception affected by thoracolumbar intervertebral disc extrusion. Materials and Methods: Data on non‐ambulatory dogs with preserved deep pain perception in both hindlimbs and surgically treated for thoracolumbar intervertebral disc extrusion were prospectively collected from three referral hospitals. Cox proportional hazards regression was used to explore the relationship of time until restoration of independent ambulation with age, weight, preoperative use of anti‐inflammatory drugs, delay between onset of inability to walk and arrival at the clinic, time between presentation and spinal surgery and surgery time. Results: One hundred and fifty‐one dogs were included. Median time from admission to surgery, including imaging, was 180 (interquartile range, 65.4 to 240) minutes. All dogs were operated within 72 hours. Follow‐up was available for all 151 dogs and ranged from 1 to 21 months. All but three dogs, which were all grade IV at presentation, recovered the ability to ambulate. In both univariable and multivariable models, only duration of surgery and neurological (Frankel) grade at presentation were significantly associated with the rapidity of recovery of ambulation. Clinical Significance: Delay between onset of clinical signs and presentation and time between presentation and spinal surgery was not associated with the rapidity of recovery of ambulation in dogs surgically treated for thoracolumbar intervertebral disc extrusion. These results should be evaluated in the context of a limited range of delay since only 14.5% dogs had a delay ≥6.5 hours. Duration of surgery and neurological grade at presentation were significantly associated with rapidity of recovery of ambulation.